(untitled)
In this paper, considering a technique used in 4, and the sequences u_kn and v_kn , we derive the sequences g_kn and h_kn . Also with the aid of generating matrix for the terms of these sequences Â for a positive integer k, we derive some conbinatorial identities for the sequence g_kn ., number=3, journal=European Journal of Pure and Applied Mathematics, year=2017, month=Apr., pages=506–515